ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENDAPATAN PEDAGANG DI PASAR TRADISIONAL BADUNG - Pego, Alfonsus Liguori Rao; Dewi, Ni Putu Martini (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 13 No 2 (2024): Vol.13.No.2. FEBRUARI 2024 [91-160]DO - 10.24843/EEP.2024.v13.i02.p01, 2024)
Traditional markets are one form of market that is still the economic center of society today. Traditional market traders are economic cogs that are important to pay attention to, especially their income. This study aims to analyze the factors that simultaneously and partially influence the income of traders in the Badung traditional market. This research at the Badung Traditional Market, due to a phenomenon indicating intense trader competition. The population with a total sample taken of 90 respondents. Data collection were analyzed using multiple linear regression by distributing questionnaires. The results of this study indicate that simultaneously market revitalization, capital, working hours and types of merchandise have effect on traders' income. Partially market revitalization, capital, working hours and types of merchandise have effect on traders' income. For traders in Pasar Badung, the results of this research can be used to optimize traders' income. This can be done by supporting market revitalization efforts, traders must optimize their capital and working hours and increase the variety of types of merchandise sold. Keywords: market revitalization, capital, working hours, types of merchandise, traders' income